2011
DOI: 10.1159/000329899
|View full text |Cite
|
Sign up to set email alerts
|

Early Intensive Obstetric and Medical Nutrition Care Is Associated with Decreased Prepregnancy Obesity Impact on Perinatal Outcomes

Abstract: Background/Aims: To compare the gestational weight gain and adverse perinatal outcomes in urban Mexican women with prepregnancy overweight or obesity, under an early intensive obstetric and nutrition program versus women with prepregnancy normal weight. Methods: A cohort of 546 pregnant women with prepregnancy normal weight (n = 201, NW), overweight (n = 171, OW) or obesity (n = 174, OB), ≤13 weeks of gestation and a singleton pregnancy. OW and OB groups were under early intensive obstetric and nutritional car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
0
7
0
3
Order By: Relevance
“…According to a prospective cohort study in the USA, GWG within the levels recommended by the Institute of Medicine (IOM) guidelines was associated with a decreased risk of delivering LBW babies [1]. In Mexico, adequate GWG decreases maternal and infant adverse outcomes [24]. In this study, the proportion of LBW in both underweight and average pregnancies based on MHLW weight gain guidelines was higher.…”
Section: Discussionmentioning
confidence: 53%
“…According to a prospective cohort study in the USA, GWG within the levels recommended by the Institute of Medicine (IOM) guidelines was associated with a decreased risk of delivering LBW babies [1]. In Mexico, adequate GWG decreases maternal and infant adverse outcomes [24]. In this study, the proportion of LBW in both underweight and average pregnancies based on MHLW weight gain guidelines was higher.…”
Section: Discussionmentioning
confidence: 53%
“…Whiteman et al [22] found in women with increasing BMI in 2 subsequent pregnancies an elevated stillbirth risk with a hazard ratio between 1.2 and 1.5 depending on BMI before the first pregnancy and weight gain between the 2 consecutive pregnancies. Reyes et al [23] showed that intense nutritional control in early pregnancy reduces the risk for perinatal adverse outcomes. Thus, obesity is an important risk factor for perinatal mortality, the impact of which can be diminished by control of maternal weight.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a recent study of women seeking prenatal care for singleton pregnancies at the National Institute of Perinatology in Mexico during 2007–2008, 17% of normal‐weight women gained above the recommended amount of weight compared to 35.7% of overweight women and 22.4% of obese women. The odds of poor maternal outcomes including gestational diabetes mellitus, preeclampsia, and lack of spontaneous initiation of labor were greatest for obese women in the sample …”
Section: Studies Published After the 2009 Iom Guidelinesmentioning
confidence: 96%